2018
DOI: 10.37358/rc.18.11.6732
|View full text |Cite
|
Sign up to set email alerts
|

Functional Results of Different Repair Techniques for Knee Articular Cartilage Lesions

Abstract: The articular cartilage lesions are frequent and highly affect the patient�s quality of life. Although remarkable progress in the treatment of focal lesions of articular cartilage were lately made, controversies still exist regarding the treatment options. The main purpose of this study was to evaluate and compare the preoperative and 6 months postoperative knee functional scores of patients undergoing arthroscopic repair of knee chondral lesions by: debridement, microfractures, osteochondral autograft transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The INION ® bioresorbable plates and pins are preferable in complex fractures of the proximal and distal humerus, fractures of peroneal malleolus, fractures of the forearm, fractures of the distal radius, knee osteochondral lesions, surgery of the forefoot and hand, fixation of bone grafts or bone substitutes [3,11,[13][14][15][16]. Their characteristics comprise: the possibility to cut the plates at the necessary length and shape depending on the patient's anatomy, the possibility of "low profile" mounting by cutting the heads of the screws, the possibility of inserting some polyaxial screws as well as radiotransparency ( fig.…”
Section: Experimental Part Inion ® Bioresorbable Plates and Pinsmentioning
confidence: 99%
“…The INION ® bioresorbable plates and pins are preferable in complex fractures of the proximal and distal humerus, fractures of peroneal malleolus, fractures of the forearm, fractures of the distal radius, knee osteochondral lesions, surgery of the forefoot and hand, fixation of bone grafts or bone substitutes [3,11,[13][14][15][16]. Their characteristics comprise: the possibility to cut the plates at the necessary length and shape depending on the patient's anatomy, the possibility of "low profile" mounting by cutting the heads of the screws, the possibility of inserting some polyaxial screws as well as radiotransparency ( fig.…”
Section: Experimental Part Inion ® Bioresorbable Plates and Pinsmentioning
confidence: 99%
“…Ex vivo studies carried out with canine cartilage suggest that its exposure to sun for 4 days leads to the loss of matrix-type cartilage [1]. Furthermore, experimental studies have shown that after a major hemarthosis, the articulation cavity is infiltrated with a dense inflammatory infiltrator, while local tissues become brownish due to the hemosiderin deposition resulting after the erythrocyte damage [2][3][4]. Vascular hyperplasia takes place, leading to the emergence of brittle vases, with a tendency towards bleeding, thus creating a vicious circle: bleeding-vascular hyperplasia-bleeding.…”
mentioning
confidence: 99%